1997
DOI: 10.1111/1523-1747.ep12336033
|View full text |Cite
|
Sign up to set email alerts
|

LAD-1 Is Absent in a Subset of Junctional Epidermolysis Bullosa Patients

Abstract: The anchoring filament protein LAD-1 has been recently identified as the target of autoantibodies in the acquired blistering disorder linear IgA bullous dermatosis. Because this protein appears to be involved in the process of dermal-epidermal cohesion, this study sought to determine the involvement of LAD-1 in the pathology of junctional epidermolysis bullosa (JEB). To this end, 44 patients with a variety of subtypes of JEB were analyzed by indirect immunofluorescence microscopy with antibodies to LAD-1, BP18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…This 120 kDa LAD antigen was found to be also recognized by IgG autoantibodies in a large number of BP sera [18,19]. The close relationship between BP180 and LAD-1 was supported by the observation that BP180-deficient tissues from patients with generalized atrophic benign epidermolysis bullosa show abnormally low or no expression of LAD-1 and do not secrete this protein into the culture medium [18,20]. Recent peptide sequence analysis and biochemical studies suggested that LABD97 and LAD-1 are generated as proteolytic cleavage products of the extracellular domain of BP180 [21][22][23].…”
Section: Introductionmentioning
confidence: 90%
“…This 120 kDa LAD antigen was found to be also recognized by IgG autoantibodies in a large number of BP sera [18,19]. The close relationship between BP180 and LAD-1 was supported by the observation that BP180-deficient tissues from patients with generalized atrophic benign epidermolysis bullosa show abnormally low or no expression of LAD-1 and do not secrete this protein into the culture medium [18,20]. Recent peptide sequence analysis and biochemical studies suggested that LABD97 and LAD-1 are generated as proteolytic cleavage products of the extracellular domain of BP180 [21][22][23].…”
Section: Introductionmentioning
confidence: 90%
“…They noted that linear IgA disease antibodies reacted with this antigen (Marinkovich et al, 1996). Further work showed that patients with generalized atrophic benign epidermolysis bullosa, who were de¢cient in BP180, also failed to show reactivity to this linear IgA disease antigen (Marinkovich et al, 1997). This suggested that this antigen is the same as BP180; however, the lack of immunoreactivity of sera with the intact BP180 antigen on immunoblot was not yet understood.…”
Section: An Animal Model Of Iga Dermotosesmentioning
confidence: 99%
“…In a recently documented form of mosaicism called revertant mosaicism (4), mutant cells undergo a second genetic event that restores protein function or expression, generating normal-appearing cells on a background of mutant cells. Although the occurrence of such revertant cells has been reported in multiple patients with Duchenne muscular dystrophy (5), tyrosinemia type I (6), Fanconi's anemia (7), Bloom's syndrome (8), and generalized atrophic benign epidermolysis bullosa (GABEB) (4,(9)(10)(11)(12)(13), the molecular basis of this mosaicism has been defined only rarely.…”
Section: Introductionmentioning
confidence: 99%